Discourse Strategies and Portrayal of Women in the Choice of Cosmetic Products in Lagos Nigeria - Michael, Adebola; Mberia, Hellen; Mutua, Joan (International Journal of Communication and Public Relation, 2023)
Purpose: The purpose of the study was to examine the effect of discourse strategies and portrayal of women in the choice of cosmetic products in Lagos Nigeria. Methodology: A mixed method design was adopted for this study using purposive sampling because this study was only to investigate cosmetic product advertisements for women. The data were collected from company websites, YouTube and outdoor ads of popularly used cosmetic products ads which were transcribed for the qualitative analysis and analyzed based on Fairclough's three-dimensional framework of Critical Discourse Analysis (CDA) while for the quantitative aspect data was collected using a questionnaire based on Likert-type scale questions to capture the different variables. They were then analyzed using descriptive statistics and inferential statistics. Findings: The study findings show that there is a statistically significant relationship between discourse strategies and portrayal of women in choice of cosmetic products in Lagos. It noted that advertisers utilise strategies such as Informing strategy, Skin Inadequacies, scientific evidences and Celebrities to influence people to choose their products. Findings affirm the direct positive of discourse strategies as R2=0.935 depicts that the model explains 93.5% of the variance thereby supporting the hypothesis that there is a significant relationship between the discourse strategies and portrayal of women in the choice of cosmetic products as the ideology of a woman wanting to look better is preyed upon by advertisers. Unique Contribution to Theory, Practice and Policy: The study was guided by CDA and theory of Imitative Desire. It reveals that there is a statistically significant relationship between discourse strategies and portrayal of women and using CDA - a kind of social practice it notes that advertisers influence the view of beauty by creating a new beauty ideology and standard derived from the Ads. Therefore, women bodies should engage in campaigns for women to value themselves, reject manipulation and advocate that adverts only reflect socially acceptable portrayals.